Students' acceptance of blog usage: Exploring the extended TAM / Norulhuda Tajuddin, Musramaini Mustapha and Azniza Ahmad Zaini - Tajuddin, Norulhuda; Mustapha, Musramaini; Ahmad Zaini, Azniza (2011)
Currently, the use of blog in academic field has been increased from time to time to assist in the teaching and learning process, Blog enables user to get and share knowledge, information, experiences and thoughts. This paper aimed to identify the intrinsic factors that motivate students to use blog in their learning process as there is only a small number of research that has been conducted to investigate the Technology Acceptance Model (TAM) model in the context of UiTM. Based on Extended TAM, there are three main variables that influence the students' attitude which are perceived usefulness (PU), perceived ease of use (PEOU) and perceived playfulness (PP), Seventy eight sets of questionnaire were distributed among second year students at the Faculty of Business Management at UiTM Pahang The result reveals positive relationships between those variables and students' attitude towards the usage of blog